2008
DOI: 10.1017/s113874160000425x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Sexual Harassment at Work: Meta-Analysis and Structural Model of Antecedents and Consequences

Abstract: Although sexual harassment has been extensively studied, empirical research has not led to firm conclusions about its antecedents and consequences, both at the personal and organizational level. An extensive literature search yielded 42 empirical studies with 60 samples. The matrix correlation obtained through meta-analytic techniques was used to test a structural equation model. Results supported the hypotheses regarding organizational environmental factors as main predictors of harassment. Keywords: sexual h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 51 publications
1
40
0
3
Order By: Relevance
“…From a conceptual point of view, we argue in line with Barling and colleagues [16] that sexual harassment can be considered a major organizational stressor. A considerable body of research indicates that sexual harassment in the workplace may have detrimental effects on employees' physical and mental health [6,9,[17][18][19]. Empirical studies investigating sexual harassment focused on relationships with indicators of impaired well-being [12,[19][20][21].…”
Section: The Effect Of Sexual Harassment On Employees' Mental Healthmentioning
confidence: 99%
“…From a conceptual point of view, we argue in line with Barling and colleagues [16] that sexual harassment can be considered a major organizational stressor. A considerable body of research indicates that sexual harassment in the workplace may have detrimental effects on employees' physical and mental health [6,9,[17][18][19]. Empirical studies investigating sexual harassment focused on relationships with indicators of impaired well-being [12,[19][20][21].…”
Section: The Effect Of Sexual Harassment On Employees' Mental Healthmentioning
confidence: 99%
“…-La aprobación en Comité de Seguridad y Salud (CSS) de un protocolo para la prevención, detección y actuación contra las situaciones de acoso sexual en las empresas, así como sus recomendaciones y procedimientos de actuación derivados, constituyen una fuente de prevención de conductas no deseadas. Ya que se ha demostrado que las características del centro de trabajo, incluyendo la gestión y estrategias, están relacionadas con el riesgo de acoso sexual (20) , incluso que los factores ambientales de la organización predicen el acoso sexual (21) .…”
Section: Discusión Y Conclusionesunclassified
“…Sexual harassment is known to have deleterious consequences on women, such as reducing psychological well-being, satisfaction, commitment, and performance of the activity involving the harassment (Cantisano, Domínguez, & Depolo, 2008;Pina & Gannon, 2006). We observed that exposure to sexualized females in video games increases online sexual harassment against female targets after the game is turned off.…”
Section: And the Social Cognitivementioning
confidence: 72%
“…We observed that exposure to sexualized females in video games increases online sexual harassment against female targets after the game is turned off. Sexual harassment is known to have deleterious consequences on women, such as reducing psychological well-being, satisfaction, commitment, and performance of the activity involving the harassment (Cantisano, Domínguez, & Depolo, 2008;Pina & Gannon, 2006).…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%